Prostate MRI – an update for the referring urologist - Czarniecki, Marcin (Cent European J Urol, 2016)
INTRODUCTION: Prostate MRI is a new and important tool which has a role in prostate cancer guidelines worldwide. The amount of articles published and studies currently taking place on the subject requires urologists to understand how the examination is performed and its possible applications. This article explains prostate MRI and standardized reporting schemes, as well as its applications according to patients’ staging and history. MATERIAL AND METHODS: The use of prostate MRI prior to biopsy, MRI-guided biopsy and its use in active surveillance, surgery staging and planning, as well as in cases with biochemical recurrence are discussed. RESULTS: The application of prostate MRI are not limited to initial diagnosis, but also has a developing role in biopsy and planning further treatment. Recently, its diagnostic applications have been included in EAU prostate cancer guidelines and new applications are in development. CONCLUSIONS: Practicing urologists are seeing an emerging role of MRI in prostate cancer. Its current and future applications may have an impact on patient care, which mandates healthcare professionals to be vigilant about the method's new developments.